OPTIMIZATION FOR SECTIONAL RETRACTION SPRING GEOMETRY SELECTION USING MEMETIC ALGORITHM WITH DATABASE - IDRIS (NIM : 23103012); Pembimbing : Dr. Ir. Rachman Setiawan; Dr. Ir. I Wayan Suweca, MUHAMMAD
One of the applications of orthodontic appliances is made of metallic wire formed to retract a tooth with respect to another by means of the spring back effect. The special form of the spring (T-loop, mushroom, U-loop) results in force (F) and moment (M) in order to move the tooth in specified movement. Thus far, the selection of the geometry depends on the knowledge and experience of the orthodontist. In this thesis, an optimization approach to the retraction spring geometry selection was proposed and implemented based on knowledge based design methodology by using memetic algorithm method. In the methodology, the function sectional retraction characteristic is based on the numerical nonlinear analysis by ANSYS and have been validated to other research. In many cases, validation results in sufficient agreement between numerical and experimental method. Based on finite element analysis of two hundred of sampling that generated by using latin hypercube sampling method, the result from 2 cases study show that the methodology can be applied in orthodontics problems and give a good representation of characteristic for sectional retraction spring. The advantages of the methodology are efficiency in optimization process so that increasing the efficiency and effectiveness in orthodontic treatment.